Photodegradation of Bisphenol A Using α-Fe2O3 Nanoparticles Synthesized by Sonochemical Assisted - Aliakbar Dehno Khalaji (Nanochemistry Research)
In this work, α‑Fe2O3 nanoparticles were prepared by sonochemical‑assisted method along with calcination at two different temperatures 500 and 700°C for 3h. The α‑Fe2O3 nanoparticles were characterized by FT‑IR, XRD, VSM and TEM. All results show that the as‑prepared α‑Fe2O3 nanoparticles are of high purity with ferromagnetic behavior, uniform distribution, and low agglomeration. In addition, photocatalytic degradation of bisphenol A (BPA) was studied by α‑Fe2O3 nanoparticles at the presence of H2O2 as an electron trap. Photocatalytic results indicate that 98% and 90% of BPA with the initial concentration of 25 mg/L in the solution were degraded using 0.02 g α‑Fe2O3 nanoparticles within 330 min under the visible light irradiation.